The Concept of Humanism in Islam and Its Problems - Metriadi Metriadi; Erizal Erizal; Zidni Ilman Nafi'an; Sri Wahyuni; Julhadi Julhadi (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2026)
This study examines the concept of humanism in Islam and its contemporary problematics within the context of community development. Employing a qualitative library research approach, the study analyzes classical and contemporary scholarly works published between 2021 and 2025, with particular attention to discussions on Islamic humanism in academic journals. The findings indicate that Islamic humanism is firmly grounded in theological and philosophical principles that emphasize human dignity (karāmah al-insāniyyah), moral responsibility, social justice, and collective accountability. Unlike secular humanism, which is largely anthropocentric, Islamic humanism is characterized by a theo-anthropocentric orientation that integrates divine values with human welfare.The study further reveals that Islamic humanism has strong relevance for community development, especially in education, social transformation, and the empowerment of marginalized groups. Nevertheless, several challenges hinder its implementation, including the gap between normative Islamic ideals and social realities, reductive interpretations that confine humanism to individual morality, and rigid textual approaches that overlook contextual and humanitarian dimensions of Islam.The novelty of this research lies in positioning Islamic humanism not merely as an ethical discourse but as an integrative normative-structural framework for community development. By emphasizing its applied and transformative dimensions, this study contributes to expanding Islamic humanism from a conceptual discourse to a practical paradigm. The study recommends strengthening contextual interpretations of Islamic teachings, integrating humanistic values into Islamic education, and employing Islamic humanism as a foundation for community empowerment and policy development to promote a just, inclusive, and sustainable society.Keywords: Islamic Humanism, Human Dignity, Community Development, Islamic Education, Social Justice